2007
DOI: 10.1089/fpd.2007.0040
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Guava (Psidium guajavaL.) and Neem (Azadirachta indicaA. Juss.) Extracts Against Foodborne Pathogens and Spoilage Bacteria

Abstract: The antibacterial activity of guava (Psidium guajava) and neem (Azadirachta indica) extracts against 21 strains of foodborne pathogens were determined--Listeria monocytogenes (five strains), Staphylococcus aureus (four strains), Escherichia coli O157:H7 (six strains), Salmonella Enteritidis (four strains), Vibrio parahaemolyticus, and Bacillus cereus, and five food spoilage bacteria: Pseudomonas aeroginosa, P. putida, Alcaligenes faecalis, and Aeromonas hydrophila (two strains). Guava and neem extracts showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 23 publications
2
37
1
Order By: Relevance
“…However, E. coli and P. aeruginosa were sensitive to all the three fruits in our study, contradicting results obtained by Qabaha [20]. Previous study showed that guava possessed the highest inhibition for L. monocytogenes , S. aureus , S. aureus , and V. parahaemolyticus [21]. Also, sweetsop extract was found to be capable of inhibiting E. coli , M. albican , S. typhimurium , Klebsiella pneumoniae , and Proteus vulgaris [22].…”
Section: Resultscontrasting
confidence: 92%
“…However, E. coli and P. aeruginosa were sensitive to all the three fruits in our study, contradicting results obtained by Qabaha [20]. Previous study showed that guava possessed the highest inhibition for L. monocytogenes , S. aureus , S. aureus , and V. parahaemolyticus [21]. Also, sweetsop extract was found to be capable of inhibiting E. coli , M. albican , S. typhimurium , Klebsiella pneumoniae , and Proteus vulgaris [22].…”
Section: Resultscontrasting
confidence: 92%
“…These results partially agree with data of the viable cell counts commented on above, where only neem oil at 10% inhibited the growth of both fungi, A. Niger and P. expansum , showing fungicidal activity after 24 h of contact. This result and those previously reported [17,40,41] justify the interest in neem oil extracts as an active additive for obtaining bioactive films. According to the lack of notable antifungal activity of the rest of tested extracts, active films were formulated with neem oil and with oregano essential oil with proved antimicrobial activity [19,22].…”
Section: Resultssupporting
confidence: 88%
“…In fact, Baswa et al [13] revealed that the neem oil has bactericidal activity against 14 strains of pathogenic bacteria such as Staphylococcus aureus [14], Staphylococcus typhus [15], and Escherichia coli , Streptococcus mutans and lactobacilli [16]. On the other hand, Mahfuzul Hoque et al [17] determined the antibacterial activity of neem extracts against 21 strains of foodborne pathogens: Listeria monocytogenes , Staphylococcus aureus , Escherichia coli O157:H7, Salmonella Enteritidis , Vibrio parahaemolyticus , and Bacillus cereus , and five food spoilage bacteria: Pseudomonas aeroginosa , Psuedomas putida , Alcaligenes faecalis , and Aeromonas hydrophila . They concluded that neem extracts generally showed higher antimicrobial activity against Gram-positive bacteria than against Gram-negative, and none of the extracts showed antimicrobial activity against E. coli O157:H7 and Salmonella Enteritidis .…”
Section: Introductionmentioning
confidence: 99%
“…Also Guava and Neem extracts showed higher antimicrobial activity against Gram-negative bacteria such as A. hydrophila (10). …”
Section: Introductionmentioning
confidence: 99%